Physiological and pathophysiological interactions between the respiratory central pattern generator and the sympathetic nervous system - Molkov, Yaroslav I.; Zoccal, Daniel Breseghello [UNESP]; Baekey, David M.; Abdala, Ana Paula L.; Machado, Benedito Honório; Dick, Thomas E.; Paton, Julian F. R.; Rybak, Ilya A. (Elsevier B.V., 2014)
Respiratory modulation seen in the sympathetic nerve activity (SNA) implies that the respiratory and sympathetic networks interact. During hypertension elicited by chronic intermittent hypoxia (CIH), the SNA displays an enhanced respiratory modulation reflecting strengthened interactions between the networks. In this chapter, we review a series of experimental and modeling studies that help elucidate possible mechanisms of sympatho-respiratory coupling. We conclude that this coupling significantly contributes to both the sympathetic baroreflex and the augmented sympathetic activity after exposure to CIH. This conclusion is based on the following findings. (1) Baroreceptor activation results in perturbation of the respiratory pattern via transient activation of postinspiratory neurons in the Botzinger complex (BotC). The same BotC neurons are involved in the respiratory modulation of SNA, and hence provide an additional pathway for the sympathetic baroreflex. (2) Under hypercapnia, phasic activation of abdominal motor nerves (AbN) is accompanied by synchronous discharges in SNA due to the common source of this rhythmic activity in the retrotrapezoid nucleus (RTN). CIH conditioning increases the CO2 sensitivity of central chemoreceptors in the RTN which results in the emergence of AbN and SNA discharges under normocapnic conditions similar to those observed during hypercapnia in naive animals. Thus, respiratory-sympathetic interactions play an important role in defining sympathetic output and significantly contribute to the sympathetic activity and hypertension under certain physiological or pathophysiological conditions, and the theoretical framework presented may be instrumental in understanding of malfunctioning control of sympathetic activity in a variety of disease states.
Keywords: Respiratory-sympathetic interactions; Baroreflex; Chronic intermittent hypoxia; Hypertension; Modeling